Normative judgments implicit in the tax system: A simulation approach - Niklas Isaak; Robin Jessen (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
How much does society value redistribution? The common method to derive inverse-optimum welfare weights is by inverting an optimal-tax model. Our alternative imposes fewer restrictions on labor supply and enables comparisons across household types. We use a structural labor supply model to calculate the marginal value of public funds for various small tax reductions, directly linked to welfare weights. An application to Germany finds: i) The tax-transfer system is optimal if society values one additional Euro for the bottom decile three times as much as for the median. ii) At low-medium incomes, weights for couples exceed those for singles substantially – – Wie viel Wert legt die Gesellschaft auf Umverteilung? Die übliche Methode zur Ableitung von invers-optimalen Wohlfahrtsgewichten besteht in der Umkehrung eines Modells mit optimaler Besteuerung. Unsere Alternative unterwirft das Arbeitsangebot weniger Beschränkungen und ermöglicht Vergleiche zwischen verschiedenen Haushaltstypen. Wir verwenden ein strukturelles Arbeitsangebotsmodell, um den Grenzwert der öffentlichen Mittel für verschiedene kleine Steuersenkungen zu berechnen, die direkt mit Wohlfahrtsgewichten verbunden sind. Eine Anwendung auf Deutschland zeigt: i) Das Steuertransfersystem ist optimal, wenn die Gesellschaft einen zusätzlichen Euro für das unterste Dezil dreimal so viel wertschätzt wie für den Median. ii) Bei niedrigen bis mittleren Einkommen übersteigen die Gewichte für Paare die für Singles erheblich.
Keywords: H21; H31; J22; 330; Inverse optimum; microsimulation; marginal value of public funds; social welfare function; optimal taxation; labor supply; efficiency